2015
DOI: 10.2337/dc14-2538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycemic and Metabolic Control in Youth With Type 1 Diabetes With and Without Antipsychotic Medication: Analysis From the Nationwide German/Austrian Diabetes Survey (DPV)

Abstract: OBJECTIVEThe objective of this study was to explore metabolic risk factors and glycemic control in youth with type 1 diabetes treated with typical or atypical antipsychotics. RESEARCH DESIGN AND METHODSData for 60,162 subjects with type 1 diabetes up to the age of 25 years registered in the nationwide German/Austrian Diabetes Survey were included in the analysis. BMI; HbA 1c ; treatment strategy; prevalence of hypertension, dyslipidemia, microalbuminuria, and retinopathy; frequency of hypoglycemia and diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
(50 reference statements)
1
22
0
2
Order By: Relevance
“…Our finding that having a psychiatric disorder is associated with compromised treatment outcomes is consistent with previous clinical (16)(17)(18)(19)(20) and populationbased studies (4)(5)(6) in pediatric populations; although previous studies have investigated individual disorders and none included the entire range of psychiatric disorders.…”
Section: Findings In Relation To Other Studiessupporting
confidence: 91%
See 4 more Smart Citations
“…Our finding that having a psychiatric disorder is associated with compromised treatment outcomes is consistent with previous clinical (16)(17)(18)(19)(20) and populationbased studies (4)(5)(6) in pediatric populations; although previous studies have investigated individual disorders and none included the entire range of psychiatric disorders.…”
Section: Findings In Relation To Other Studiessupporting
confidence: 91%
“…We found that having a psychiatric diagnosis from the potentially reactive disorder group or a combination of both types of disorder was associated with higher HbA 1c levels. In comparison, the German/Austrian diabetes register study generally found greater differences in metabolic outcome (0.3-0.8% [3.5-9 mmol/mol]) when they investigated individual diagnoses (4)(5)(6).…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 94%
See 3 more Smart Citations